A new development of four-point method to measure the electrical resistivity in situ during plastic deformation. (August 2021) - Saberi, Saeid; Stockinger, Martin; Stoeckl, Christian; Buchmayr, Bruno; Weiss, Helmut; Afsharnia, Reza; Hartl, Karin
Highlights: In situ measurement of electrical resistivity during plastic deformation. The electrical resistivity of metal sheets strongly depends on strain history. Change of electrical resistivity during plastic deformation is significant. The variation of electrical resistivity is affected by strain path. Development of Four- point method for in situ measurement of resistivity. Abstract: The presented study introduces a new test method to measure the change of the electrical resistivity in situ during plastic deformation to characterize the deformation behaviour of metals. This investigation is based on a specially developed four- point method, which determines the change in electrical resistance of sheet samples of an aluminium alloy 6062, a copper alloy CW024A and steel DC04 in situ during deformation in a tensile test. Results show that the strain path, the deformation history, the plastic anisotropy as well as the plastic deformation have a significant influence on the electrical resistivity of all investigated materials. Therefore, this technique is universally applicable for all sheet metals, independent of the crystal structure, the electrical and mechanical properties to characterize structural changes during forming. The obtained data can be used for simulations of metal forming processes, e. g. to predict forming limit curves and damage monitoring under service loading.